Exploring the effect of Yinzhihuang granules on alcoholic liver disease based on pharmacodynamics, network pharmacology and molecular docking - Yingying Tan; Fanqin Zhang; Xiaotian Fan; Shan Lu; Yingying Liu; Zhishan Wu; Zhihong Huang; Chao Wu; Guoliang Cheng; Bing Li; Jiaqi Huang; Antony Stalin; et al. (BMC, 2023)
Abstract Background Yinzhihuang granules (YZHG) is a commonly used Chinese patent medicine for the treatment of liver disease. However, the mechanism of YZHG in alcoholic liver disease (ALD) is still unclear. Methods This study combined liquid chromatography-mass spectrometry technology, pharmacodynamics, network pharmacology and molecular docking methods to evaluate the potential mechanism of YZHG in the treatment of ALD. Results A total of 25 compounds including 4-hydroxyacetophenone, scoparone, geniposide, quercetin, baicalin, baicalein, chlorogenic acid and caffeic acid in YZHG were identified by ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS). The pharmacodynamic investigations indicated that YZHG could improve liver function and the degree of liver tissue lesions, and reduce liver inflammation and oxidative stress in ALD mice. Network pharmacology analysis showed that YZHG treated ALD mainly by regulating inflammation-related signaling pathways such as the PI3K-Akt signaling pathway. The results of the PPI network and molecular docking showed that the targets of SRC, HSP90AA1, STAT3, EGFR and AKT1 could be the key targets of YZHG in the treatment of ALD. Conclusion This study explored the potential compounds, potential targets and signaling pathways of YZHG in the treatment of ALD, which is helpful to clarify the efficacy and mechanism of YZHG and provide new insights for the clinical application of YZHG.